Improved Steel Beam-Column Connections in Industrial Structures - Bishay-Girges, N. W. (Engineering, Technology & Applied Science Research, 2020)
Beam-to-column connection is a rigid connection used in steel moment frames which acts as the main resisting system in structural design. Haunches with double beam section height at the eave, ridge and crane bracket are usually used to resist the large bending moment at the critical locations of the steel frames. Damper devices can be used as the main source of producing forces used to reduce the bending moment due to different static and dynamic loads. This study focuses on improving the steel beam-column connection with the proposed control system in the eave connection which can also be used under the bracket which supports crane beam in industrial buildings. The purpose of this study is to describe the development of the beam-column steel connection incorporating dampers installed to beam bottom flange to reduce the effect of applied load on the frame without the need to create haunches to make the connection design more efficient.